MODEL MANAJEMEN RANTAI PASOKAN PADA UMKM SURABAYA - Nainggolan, Romauli (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2018)
There are 3,947 MSMEs registered in Surabaya city government. There are 3,947 MSMEs registered in Surabaya city government. 174 MSMEs in the area of West Surabaya. Activities of MSMEs from suppliers to customers was simply. It can be seen by observing 30 SMEs in western Surabaya. It can be seen by observing 30 SMEs in West Surabaya. The results of research there are 2 things (1) implementation of suppliers strategy, MSMEs in West Surabaya using strategy with 1 supplier is 10%. MSMEs in West Surabaya using strategy with 2 suppliers is 40%. MSMEs in West Surabaya using strategy with 3 suppliers is 40%. MSMEs in west Surabaya use many suppliers strategy with 4 - 5 suppliers that is 10%. (2) There are 4 supply chain management models. First, supplier – manufacturer - consumer. Second, suppliers – manufacturer-retailer – consumer. Third, supplier - distributor- customer. Fourth, supplier-retailer – consumer. Owners of MSMEs buy their own raw materials from the market, shops, shopsnearby. Then they do the manufacturing process by making their own products and directly sell them to consumers or sell them to new retailers to consumers.